Analisis Pemilihan Umum Proporsional Terbuka Dan Tertutup di Indonesia - Intan kumala dewi; Sandra Dewi; Yesyka; Nur fajarriah; Nilam Permata Sari; Dewi Haryati (Lembaga Pengembangan Kinerja Dosen, 2024)
The electoral system is a form of representative democracy which can be understood as a means of distributing power to the people. In general, there are three types of electoral systems implemented throughout the world, namely majority systems, proportional systems and mixed systems. However, this article only discusses open and closed elections, each of which has its own advantages and disadvantages. This article aims to analyze the open and closed proportional electoral systems in Indonesia. The type of research used is legal research by considering the problems of studying documents used as reference documents, especially legal regulations such as basic legal documents and other secondary legal documents such as literature, books, scientific works and scientific articles. which discusses how to analyze open and closed proportional electoral systems in Indonesia.